2018
DOI: 10.1016/j.jaut.2017.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Innately versatile: γδ17 T cells in inflammatory and autoimmune diseases

Abstract: IL-17-producing γδ (γδ17) T cells form a versatile subset of cells that respond rapidly to innate stimuli and support the pro-inflammatory functions of different myeloid and lymphoid lineages, being particularly critical in the early stages of inflammatory and autoimmune responses. In mice, under homeostatic conditions, these innate-like lymphocytes are pre-programmed in the fetal thymus, through an intricate process involving both T cell receptor-dependent and -independent signals, which allows them to readil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
81
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 97 publications
(85 citation statements)
references
References 166 publications
4
81
0
Order By: Relevance
“…Indeed, γδKO allograft recipients formed fewer autoantibodies upon ApoExo injection and showed lower expression of IL‐17 within vascular allografts and reduced TLS formation. These observations are in line with previous studies showing that human IL‐17‐producing γδT cells are generated in the periphery and can be recruited to inflamed tissues where they accumulate . This process takes place more rapidly compared to the activation of conventional T lymphocytes as γδT cells can be activated in the absence of a cognate TCR ligand .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Indeed, γδKO allograft recipients formed fewer autoantibodies upon ApoExo injection and showed lower expression of IL‐17 within vascular allografts and reduced TLS formation. These observations are in line with previous studies showing that human IL‐17‐producing γδT cells are generated in the periphery and can be recruited to inflamed tissues where they accumulate . This process takes place more rapidly compared to the activation of conventional T lymphocytes as γδT cells can be activated in the absence of a cognate TCR ligand .…”
Section: Discussionsupporting
confidence: 91%
“…33 γδT cells are generated in the periphery and can be recruited to inflamed tissues where they accumulate. 36,37 This process takes place more rapidly compared to the activation of conventional T lymphocytes 38 as γδT cells can be activated in the absence of a cognate TCR ligand. 38 The mechanism by which ApoExo activate γδT cells is still ill defined, but our results identify the proteasome activity of ApoExo as a pivotal signal regulating trafficking of γδT cells to sites of vascular injury.…”
Section: The Proteasome Activity Within Apoexo Is Required For Indumentioning
confidence: 99%
“…Inflammatory Bowel Disease (IBD), psoriasis and asthma etc.) and neurodegeneration along with tissue homeostasis and repair [194][195][196][197][198][199]. γδT cells constitute minor (2%-10% of CD3 + T cells) but a very important component of the T-cell population in peripheral circulation in humans.…”
Section: Gamma Delta (γδ) T Cells In Inflammatory Diseases and Their mentioning
confidence: 99%
“…Identication of differentially abundant immune cell subsets offers a glimpse into potential immune mechanisms contributing to PBC. Gamma-delta T cells are non-conventional T cells with a restricted T cell receptor repertoire often conceived as forming a bridge between innate and adaptive immunity 20 . In our study, the peripheral gamma-delta T cell population was found to be reduced in PBC compared to controls, visually on the FlowSOM-MST map and quantitatively in FlowSOM metacluster and cluster analyses.…”
Section: Discussionmentioning
confidence: 99%